La asociación bentónica del Bivalvo Miocénico Nuculana fundationis: índice de condiciones disaeróbicas en sedimentos clásticos finos - Fischer, Rudolf (2011)
A fauna of benthic bivalvs, recolectced from pelitic rocks of the Roca Carballo Member (Punta Carballo Formation) near Esparza, Puntarenas Province, Costa Rica, is composed of autochthonous and parautochthonous elements. The assemblage, characterized by low diversity and equity, is part of a former biocenosis. N. (Nuculana) fundationis n.sp. is the principal element of the association and is accompanied by Harvella aff. sincola, Caryocorbula oropendula, Chione falconensis, Dosinia delicatissima, Tagelus cebus and Anadara singewaldi. Other species of bivalvs are rare and facultative elements. The association colonized the soft, grained subtrate of an subtidal estuary, wherein poikilo-aerobic conditions governed.